Food-borne diseases – a freguent problem in ordinary clinical practice - Gładysz, Andrzej; Pazgan-Simon, Monika; Fleischer, Katarzyna (Przewodnik Lekarza/Guide for GPs, 2006)
Food-borne diseases are a frequent problem in ordinary clinical practice. A food-borne disease is an acute gastroenterocolitis induced by consumption of food contaminated with bacteria, toxins, parasites or fungi. Rotaviruses are a common cause of food-borne diseases in children. Adults suffer from diseases caused by Salmonella spp., Campylobacter spp., and Staphylococcous aureus . Trichinellosis or Clostridium botulinum toxin induced poisoning is observed rarely. The most common symptoms are diarrhoea, vomiting and dehydration. In diagnostics, anamnesis and physical examination are the most essential, while blood examination and microbial examination are used less often. In treatment, rehydration, realimentation and probiotics are most important; antibiotic therapy is used only when necessary. It is important to remember that food-borne diseases may lead to large-scale pathology.